I mmunosenescence and Inflammaging: Risk Factors of Severe COVID-19 in Older People - Pietrobon, Anna Julia; Teixeira, Franciane Mouradian Emidio; Sato, Maria Notomi (Frontiers in Immunology, 2020)
Old individuals are more susceptible to various infections due to immunological changes that occur during the aging process. These changes named collectively as “immunosenescence” include decreases in both the innate and adaptive immune responses in addition to the exacerbated production of inflammatory cytokines. This scenario of immunological dysfunction and its relationship with disease development in older people has been widely studied, especially in infections that can be fatal, such as influenza and, more recently, COVID-19. In the current scenario of SARS-CoV-2 infection, many mechanisms of disease pathogenesis in old individuals have been proposed. To better understand the dynamics of COVID-19 in this group, aspects related to immunological senescence must be well elucidated. In this article, we discuss the main mechanisms involved in immunosenescence and their possible correlations with the susceptibility of individuals of advanced age to SARS-CoV-2 infection and the more severe conditions of the disease.